2012
DOI: 10.1080/10962247.2012.687704
|View full text |Cite
|
Sign up to set email alerts
|

NO2 and SO2dispersion modeling and relative roles of emission sources over Map Ta Phut industrial area, Thailand

Abstract: Map Ta Phut industrial area (MA) is the largest industrial complex in Thailand. There has been concern about many air pollutants over this area. Air quality management for the area is known to be difficult, due to lack of understanding of how emissions from different sources or sectors (e.g., industrial, power plant, transportation, and residential) contribute to air quality degradation in the area. In this study, a dispersion study of NO 2 and SO 2 was conducted using the AERMOD model. The areaspecific emissi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 14 publications
1
17
0
Order By: Relevance
“…AERMET requires both surface meteorological data to drive its surface energy balance module and morning upper-air data for its daytime mixing height calculation in which mixing height increases due to sensible heat transferred from the surface to the atmospheric boundary layer. The configuration and implementation of AERSURFACE and AERMET here follow those in Chusai et al (2012) mostly, with some adjustment to suit our Chon Buri application.…”
Section: Photochemical Box Model and Simulation Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…AERMET requires both surface meteorological data to drive its surface energy balance module and morning upper-air data for its daytime mixing height calculation in which mixing height increases due to sensible heat transferred from the surface to the atmospheric boundary layer. The configuration and implementation of AERSURFACE and AERMET here follow those in Chusai et al (2012) mostly, with some adjustment to suit our Chon Buri application.…”
Section: Photochemical Box Model and Simulation Setupmentioning
confidence: 99%
“…Based on a three-day back-trajectory examination using the HYSPLIT model (Draxler and Hess, 1998; http://www.arl. noaa.gov/HYSPLIT.php) (details not shown), the trajectory paths of air mass arriving at the city center in the afternoon of both episodes do not pass through any nearby highly polluted or large cities, that is, Bangkok metropolitan (PCD, 2001) to the northwest of the city, and Rayong (Chusai et al, 2012;Phan and Manomaiphiboon, 2012) to the south-southeast. Also, they do not pass through any other large cities in Thailand and neighboring countries.…”
Section: Photochemical Box Model and Simulation Setupmentioning
confidence: 99%
“…The RHC is preferred to the actual peak value and represents a rounded estimate of the highest concentrations, based on a tail exponential fit to the upper end of the distribution. With this procedure, the effect of extreme values on model comparison is reduced [11]. Results from robust highest concentration indicated that AERMOD provided slightly better result in predicting extreme end of SO2 concentration than CALPUFF (percentage of overall difference in RHC from AERMOD was about 33 % while this value from CALPUFF prediction was about 35%).…”
Section: Resultsmentioning
confidence: 87%
“…Therefore, their analysis of change was limited to a short time span. A research study conducted in the Map Ta Phut industrial zone has examined the spatial dispersion of NO 2 and SO 2 in relation to point sources [36]. This research used a high resolution land cover data set, documenting the status of Map Ta Phut in 2007 and a spatial model called AERMOD (American Meteorological Society-Environmental Protection Agency Regulatory Model).…”
Section: Methodsmentioning
confidence: 99%